(untitled) (Lingue e culture dei media, 2019)
Blasphemies and insults against religious figures have entered everyday life, a tendency increasingly mirrored in American-English films. This paper firstly explores whether this statement is true and, in that case, it analyses how religious swearwords are rendered in Italian films. To this aim, a corpus of mostly American films dating from 1974 to 2015 has been created. What emerges from the analysis, is that Italian translators tend to omit blasphemies owing to self-censorship, legal constraints, and/or social non-acceptance. Epithets against religious figures are among the worst swearwords an Italian could hear or utter. For this reason, foul language is generally lessened or turned into mere appeals to divinities. In other instances, a shift to scatology or sex takes place. This paper’s findings reveal that, in most cases, the swearwords uttered do not do justice to the dramatic or tense situation a film character is experiencing. A call for more creative solutions and the urge to resort to authentic euphemisms will finally be stressed, given the vast repertoire of Italian substitutes for blasphemies.